Assessment of the physicochemical properties of drinking water of selected schools in Kuwait / Khaled Mageed Ahmad A E Al Qattan - Khaled Mageed , Ahmad A E Al Qattan (2017)
The drinking water is the most important natural element in eco system which cannot be ideally utilized and managed unless its quality is appropriately evaluated. Despite the efforts made in the best use of technology to ensure delivery of high-quality water to consumers, governments in the most countries still need to intensify efforts to promote and follow-up field studies with continuous improvement of guidelines standards. The predominant hyper-dry climate of Kuwait is not positive to the presence of any waterway frameworks in the nation, inward renewable groundwater sources are negligible so that Kuwait's main source is from Bay of Kuwait supplied by desalination plants. The main objectives of this study are, first, to characterize tap drinking water quality of 51 selected schools in Kuwait, and second, to assess the physicochemical properties of drinking water in Kuwait with national, regional and international standards, Data for drinking water is extracted selected schools in different residential areas in 5 Governorates of Kuwait. A total of analyzed data reading is 3015 monthly average collected during a period of 12 months of 2014. A third, objective is to suggest improved national standards of physicochemical properties of tap water comparing with international standards. Data from secondary data were provided by the Environmental Public Authority-State of Kuwait, The physicochemical parameters were analyzed using Microsoft Excel Version 2010, Descriptive statistics methods was used for quantitative variables analysis and multivariate Statistical Methods with the objective of evaluating significant differences among the sites for all water quality variables. The results show that the concentrations of most physical parameters were within the recommended limits concentrations except the temperature reaching a mean value of 32.31±5.35 °C. This value is 3 times higher than the desirable water temperature of 4 °C to 10 °C and is directly related to the natural hot weather condition. Most of the chemical parameters such as TOC, TA and major cations and anions as Ca2+, Mg2+, Na+, F–, Cl–, NO3– , SO42–, and trace metals such as Al, As, Ba, Cd, Cr, Cu, Pb, Mn, Hg, Ni, Zn were the concentrations in tap drinking water below threshold values stipulated by most national, regional and international agencies. However the analysis results revealed the maximum average concentration of Cl were at 0.55 mg/l of the samples investigated thus exceeding the allowable set standards. However the means of all the samples were at 0.25±0.06 mg/l. while the mean values lower between all five governorates. Trace metal such as Se mean concentration varied between 5 μg/l and 29.9 μg/l. while the means of all the samples was at 6.95±6.37 mg/l. The maximum concentration was higher than the national standard value of KUW-EPA of 10 μg/l, whereas it is lower than the standards of GSO and WHO set at 40 μg/l.